Pemanfaatan Biochar Untuk Meningkatkan Produktivitas Lahan Sub Optimal - Niluh Putu Sri Ratmini; Yuana Juwita; Priatna Sasmita (Seminar Nasional Lahan Suboptimal, 2018)
Sriratmini et al, 2019. Utilization of Biochar to Increase Sub Optimal Land Productivity. pp. 502-509. Biochar obtained through the incomplete combustion and minimum oxygen, the material used can be agricultural wastes obtained from around us. Utilization of agricultural waste provides two functions, namely as a function of the environment and also the function of land fertility, especially suboptimal land. Utilization of suboptimal land as agricultural land is constrained by the physical, chemical and biological properties of the soil. This paper discusses some of the functions of biochar associated with increasing suboptimal land productivity both physically, chemically and biologically. From the results of some literature is known that the role of biochar will be greatly influenced from the combustion process, combustion temperature, source of raw materials used, the type of soil and and how the application. Biochar applications on suboptimal land can improve soil chemical properties, soil biology and soil physical properties. Improvement of soil properties will improve land productivity and crop productivity.